Iranian EFL learners' writing ability and writing strategies in two discourse types / Farhad Fahandej Saadi - Saadi, Farhad Fahandej (2013)
This study investigated the writing strategies of Iranian EFL learners with different levels of writing ability in narrative and argumentative essays. Three good writers and three poor writers were selected from 32 initial volunteers based on their level of proficiency. Data were gathered from these participants in two writing tasks through four different sources, namely think aloud protocols, stimulated recalls, post-writing interviews, and their written products. The strategic behaviors of each individual writer were initially derived from single case analyses. After that, cross case analyses were performed across different writing tasks and different groups of writers. The findings revealed that writing was a complicated recursive process of meaning discovery. Both groups of writers used certain writing strategies in combination to approach the different tasks, interact with the texts, generate new ideas, and modify their texts. The degree of recursiveness was different between good writers and poor writers. The two groups of writers were found to employ different writing strategies in the way they interact with the emerging text, ability to see their text as a whole, concentrating on meaning, and lowering cognitive load. Another difference between the two groups of writers was that the poor writers followed almost the same writing behaviors across two different writing tasks while the good writers appeared to modify the way they composed different writing tasks.